Mutation of hemA gene of shigella flexneri: towards development of an oral live attenuated shigella vaccine - Yi, Chang Yang (Universiti Sains Malaysia, 2008)
Shigella is one of the most important causes of gastroenteritis and death of 3-5 millions of children under the age of 5 years in developing countries (Ashkenazi, 2004; Raqib et al., 2006; Sur et al., 2004). Even though antibiotics are generally effective against shigellosis, but Shigella are increasingly developing antibiotic resistance, even to the newest antibiotics (Ashkenazi et al., 2003). Therefore the World Health Organization has given priority to the development of a safe and effective vaccine against Shigella. (Kotloff et al., 1999} Shigellosis, which continues to have an important global impact, cannot be adequately controlled with the existing prevention and treatment measures. One of the ways of prevention is to interrupt the metabolic pathway of Shigella. Shigella jlexneri poses a metabolic gene, hemA which encodes for glutamyl-tRNA reductase enzyme. This enzyme catalyzes the formation of glutamate-I -semialdehyde from glutamyl-tRNA Glu and NADPH m prophyrin biosynthesis. Therefore, in this study hemA gene will be mutated by insertional mutation technique. The most likely effect of the hemA mutation is to block or retard the growth of Shigella jlexneri in an aerobic in vivo environment. Such mutants will induce protective immunity against shigellosis. In the present study, hemA gene has been successfully mutated with a kanamycin gene cassette (aphA) and the construct was successfully subcloned into a conjugative suicide vector, p WM91. The use of the antibiotic gene cassette is to facilitate the process of manipulating the genes as it serves as a selective marker. The construction of hemA::aphA thus will facilitate the development of a potential vaccine strain of Shigella jlexneri.